PERAN KUALITAS AUDIT DALAM HUBUNGAN KEPEMILIKAN KELUARGA DAN KEPEMILIKAN INSTITUSIONAL DENGAN PENGHINDARAN PAJAK - Salma Afrilia (2021)
This study aims to analyze the role of audit quality in the relationship between family ownership and institutional ownership with tax avoidance in listed manufacturing companies in the Indonesia Stock Exchange in 2017-2019. This study is a quantitative research using random effect model. This study uses secondary data in the form of company annual reports. Sample of this study is 71 manufacturing companies. The data analysis technique used are the regression model selection test, classic assumption test, multiple regression analysis test, and hypothesis testing. The results of data analysis indicate that (1) family ownership has a significant positive effect on tax avoidance, (2) institutional ownership has a significant negative effect on tax avoidance, (3) audit quality has no role in weakening the relationship between family ownership and tax avoidance, and (4) audit quality has no role in strengthening the relationship between institutional ownership and tax avoidance.